PENGEMBANGAN KOMIK FABEL UNTUK MEDIA KOMUNIKASI DAN SUPLEMEN PENDIDIKAN LINGKUNGAN DALAM RANGKA KAMPANYE PELESTARIAN KEANEKARAGAMAN HAYATI DI KAWASAN PENYANGGA TAMAN NASIONAL WAY KAMBAS-LAMPUNG - Ida Nurhaida; Agus Setiawan; Samsul Bakri; Gede A.B. Wiranata; Pairul Syah (Bumi Lestari Journal of Environment, 2011)
The severity of human-wildlife conflict in buffer zone of The Way Kambas National Park (WKNP) Lampung Indonesia is a symptom of the biodiversity deterioration undergoing in the region. The absentia of local knowledge, lack of migrant’s knowledge about the intangible relation between land productivity degradation and biodiversity loss, the stagnation of ecological knowledge cascading to their migrant’s off spring are the special challenge both for communication development planners and educators to design communication medium or teaching material so that the cascading process works well. This research was objected to develop fable as communication medium or teaching material for elementary school especially for the local issues compatibility. This research consisted of field work and laboratory exercises from April to September 2008. The fieldwork was conducted in three villages in buffer zone of the District of East Lampung i.e: Brajayekti, Braja Luhur, and Braja Asri villages as the representation of Balinese, Javanese, and Sundanese respectively. The laboratory activities were conducted at the Lab of Photography and Lab of Multimedia of the University of Lampung. The essential messages contents were extracted from the previous research results (Nurhaida et al., 2007a and 2008a). The development of story setting, story boarding, graphical sketching, lettering, typographic and lay outing for the fable design were conducted by brain storming and discussion among us, the researchers. Whereas for graphical drawing was ordered to a professional painter. The graphical symbols were reproduced by digital camera then manipulated using computer software of Adobe Photoshop. Very firstly, Bahasa Indonesia was applied as the language then we translated to Balinese, Javanese and Sundanese languages. Draft of a-40 page of comic fable was printed on glossy white papers of A5 dimension. The media pre testing conducted by following Bertrand (1978 as adopted by Nurhaida, 2001 and 2007a) to measure the fabels’ effectiveess (their attraction, their self-involvement, their acceptability and their comprehension) for the elementary students. The results showed that the media reliability in conveying those messages were 78.4%; 78.7%; 79.0% and 79.9% for edition of the Bahasa Indonesia, the Javanese, the Sundanese, and the Balinese respectively. Because the readability of the student was in low continum i.e. 61.5 [Sd=13.8] words per minute, the media were considered as reliable for conveying the messages. It is strongly recommend that use media for extension program and teaching material for the aim at promoting biodiversity in NPWK bufferzone. Adapting the media for applying in the 23 other deteriorated Indonesian national parks’ bufferzone is strongly recommended as well.